Biosynthesis and release of phospholipids by fibroblast-like synoviocytes from human osteoarthritic knee joint - Sluzalska, Katarzyna Dominika; Justus Liebig University Giessen (My University, 2017)
In human joints phospholipids (PLs) are produced and released by fibroblast-like synoviocytes (FLS). However, the regulatory mechanism of these processes remains poorly understood. Elevated levels of cytokines and growth factors as well as of PLs were found in synovial fluid (SF) during osteoarthritis (OA). Therefore, we hypothesized that PL metabolism in FLS is regulated by various agents being present in OA SF. This study aimed to develop two in vitro modelst o study the biosynthesis and release of PLs in ordert o evaluate the effects of cytokines, growth factors and drugs on PL metabolism. To measure the biosynthesis of PLs, FLS were cultured in DMEM containing 5% lipoprotein deficient serum in the presence of stable isotope-labelled precursors of PLs and various agents. To study the release of PLs, FLS were cultured in DMEM containing 10% FBS in the presence of radiolabelled precursors of PLs. Cells were starved and the release of radiolabelled PLs was determined in DMEM containing 2% FBS in the presence of agents tob e tested. Lipids were extracted from cellular lysates and media, and then quantified using electrospray ionization tandem mass spectrometry in the biosynthesis model or liquid scintillation counting in the release model. The results of our lipidomic study provide fort he first time a detailed overview of PLs being synthesized and released from human FLS. We were able to demonstrate that IL-1ß induced the biosynthesis of phosphatidylethanolamine (PE) and PE-based plasmalogens (PE P), whereas TNFa induced only the biosynthesis of PE. Also, BMPs induced the biosynthesis of several PE and PE P species. In vivo PE P could protect against cartilage destruction mediated by ROS, whereas elevated PE could induce apoptosis of hypertrophic FLS and osteophytes. Furthermore, growth factors such as TGF-ß1, IGF-1, and BMP-2 upregulated the biosynthesis of phosphatidylcholine (PC) which in vivo could be responsible for joint lubrication as well as mediation of the signal transduction. Additionally, dexamethasone was found to decrease the biosynthesis of PE. Moreover, we demonstrated that the release of radiolabelled PLs is a time-dependent process. However, tested agents did not influence the release of PLs using our in vitro model. Thus, the mechanism controlling PL release needs tob e further investigated. In conclusion, our results indicate that cytokines and growth factors regulate PL biosynthesis and may contribute tot he altered PL composition in OA SF. Moreover, our data suggest that FLS undergo PL alterations to adapt tot he new diseased environment. Understanding intra- and extracellular functions of elevated PLs within human articular joints is a new challenge for lipidomic studies.

In menschlichen Gelenken werden Phospholipide (PLs) durch Fibroblasten-ähnliche Synoviozyten (FLS) produziert und freigesetzt. Der regulatorische Mechanismus dieser Prozesse bleibt jedoch schlecht verstanden. Erhöhte Konzentrationen von Zytokinen und Wachstumsfaktoren sowie PLs wurden in Synovialflüssigkeit (SF) bei Osteoarthritis (OA) gefunden. Daher haben wir vermutet, dass der PL-Metabolismus in FLS durch verschiedene Substanzen reguliert wird, die in der pathologischen SF vorhanden sind. Diese Studie zielte darauf ab, zwei in vitro-Modelle zu entwickeln, um die Biosynthese und Freisetzung von PLs zu untersuchen, um die Auswirkungen von Zytokinen, Wachstumsfaktoren und Medikamenten auf PL-Metabolismus zu bewerten.Um die Biosynthese von PLs zu messen, wurden FLS in DMEM, das 5% Lipoprotein-defizientes Serum enthielt, in Gegenwart von stabilen isotopenmarkierten Vorläufern von PLs und mit verschiedenen Substanzen kultiviert. Um die Freisetzung von PLs zu untersuchen, wurden FLS in DMEM mit 10% FBS, in Gegenwart von radioaktiv markierten Vorläufern von PLs kultiviert. Die Zellen wurden ausgehungert und die Freisetzung von radioaktiv markierten PLs wurde in DMEM mit 2% FBS, in Gegenwart von zu testenden Substanzen bestimmt. Die Lipide wurden aus zellulären Lysaten und Medien extrahiert und dann unter Verwendung von Elektrospray-Ionisations-Tandem-Massenspektrometrie im Biosynthese-Modell oder einer Flüssigkeitsszintillationszählung im Freisetzungsmodell quantifiziert.Die Ergebnisse unserer lipidomischen Studie liefern erstmals einen detaillierten Überblick über PLs, die synthetisiert und aus humanem FLS freigesetzt werden. Wir konnten nachweisen, dass IL-1ß die Biosynthese von Phosphatidylethanolamin (PE) und PE-basierten Plasmalogenen (PE P) induzierte, während TNFa nur die Biosynthese von PE induzierte. Auch BMPs induzierten die Biosynthese von mehreren PE- und PE P-Spezies. In vivo könnte PE P gegen die durch ROS vermittelte Knorpelzerstörung schützen, während erhöhte PE eine Apoptose von hypertrophischen FLS und Osteophyten induzieren könnte. Darüber hinaus haben Wachstumsfaktoren wie TGF-ß1, IGF-1 und BMP-2 die Biosynthese von Phosphatidylcholin (PC), die in vivo für die Gelenkschmierung sowie die Vermittlung der Signaltransduktion verantwortlich sein könnten, hochreguliert. Zusätzlich konnte gezeigt werden, dass Dexamethason die Biosynthese von PE verringert. Darüber hinaus haben wir gezeigt, dass die Freisetzung von radioaktiv markierten PLs ein zeitabhängiges Verfahren ist. Allerdings beeinflussten die getesteten Wirkstoffe die Freisetzung von PLs nicht in unserem in vitro Modell. Somit muss der Mechanismus
Keywords: ddc:610